Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = \dfrac { 2 x + 1 } { 4 }$
$y = \dfrac { x - 3 } { 3 }$
$x$Intercept
$\left ( - \dfrac { 1 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , \dfrac { 1 } { 4 } \right )$
$x$Intercept
$\left ( 3 , 0 \right )$
$y$Intercept
$\left ( 0 , - 1 \right )$
$\dfrac{ 2x+1 }{ 4 } = \dfrac{ x-3 }{ 3 }$
$x = - \dfrac { 15 } { 2 }$
 Solve a solution to $x$
$\color{#FF6800}{ \dfrac { 2 x + 1 } { 4 } } = \color{#FF6800}{ \dfrac { x - 3 } { 3 } }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = \color{#FF6800}{ 4 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
$\color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = 4 x - 12$
 Multiply each term in parentheses by $3$
$\color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = 4 x - 12$
$\color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 3 = 4 x - 12$
 Simplify the expression 
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } + 3 = 4 x - 12$
$6 x + 3 = \color{#FF6800}{ 4 } \color{#FF6800}{ x } - 12$
 Move the variable to the left-hand side and change the symbol 
$6 x + 3 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } = - 12$
$6 x \color{#FF6800}{ + } \color{#FF6800}{ 3 } - 4 x = - 12$
 Move the constant to the right side and change the sign 
$6 x - 4 x = - 12 \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
$\color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ x } = - 12 - 3$
 Organize the expression 
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = - 12 - 3$
$2 x = \color{#FF6800}{ - } \color{#FF6800}{ 12 } \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
 Find the sum of the negative numbers 
$2 x = \color{#FF6800}{ - } \color{#FF6800}{ 15 }$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 15 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 15 } { 2 } }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture